ANALISIS TINGKAT KEPUASAN NASABAH PENGGUNA E-BANKING PADA MASA PANDEMI COVID-19 - Aiyubbi, Dityawarman El; Trisanty, Aidha; Wijayanti, Diana (Banking & Management Review, 2021)
This study aims to determine how the level of customer satisfaction in e-banking users during the Covid-19 pandemic. The analysis conducted using the Customer Satisfaction Index (CSI) shows a satisfaction index value of 74.75 per cent, which means that it is in the satisfied criteria. Meanwhile, Importance Performance Analysis (IPA) shows that seven items fall into the category that needs to be maintained: Complete features, practicality and effectiveness, accuracy and speed, security and convenience, deep location coverage, sophisticated, up-to-date and modern information technology, and carrying out procedures following Bank Indonesia regulations and the Financial Services Authority. Then three items fall into the low priority category: ease of activation, interface display, and low transaction fees.